Arsenite Induced Conformational Changes and Aggregation in Human Serum Albumin (HSA) and its Prevention by Naringin - Fatima, Shamila; Arshad, Fareeha; Amani, Samreen (Current Proteomics, 2022)
Background: Heavy metals and metalloids like arsenic, cadmium, mercury acts as denaturing agent for biomolecules. They interfere with protein’s physiological activity by forming a complex with the protein’s side chain or removing the essential metal ions from metalloproteins and replacing them. Protein aggregation is an extensive phenomenon in a cell and is linked with various pathological conditions. Aim: In this study, we aim to prove that proteins are highly susceptible to arsenite toxicity by arsenite-induced protein aggregation; and that naringin reduces the aggregation effect. Methods: Several biophysical techniques were employed to study the protein aggregation due to arsenite and its prevention by naringin. Results: Through our experiments, the results showed that aggregation induced by arsenite was reduced in the presence of naringin at twice the concentration of arsenite. Conclusion: In conclusion, our study showed that naringin plays a protective role during HSA aggregation due to arsenite.
Keywords: HSA